2016
DOI: 10.1021/acs.inorgchem.6b02229
|View full text |Cite
|
Sign up to set email alerts
|

Facile Way of Synthesis for Molybdenum Iodides

Abstract: Molybdenum iodides are prepared based on a new way of synthesis, namely, via reductive metathesis reaction of MoCl with SiI. MoI was formed at 150 °C. MoI and the new molybdenum iodides MoI and MoI with the well-known [MoI] cluster core were obtained in the temperature range 550-600 °C. Compounds were structurally characterized by powder and single-crystal X-ray diffraction techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…It has been claimed since a long time that MoI 3 is isostructural with MoBr 3 , and thus possesses polymeric chains built of MoI 6 octahedra with shared opposite faces: 1 [MoI 6/2 ]∞ with short Mo–Mo bonds along the chain , . This was recently confirmed by careful refinement of the powder diffraction pattern from a sample of MoI 3 obtained by reductive iodination of MoCl 5 with SiI 4 at 150 °C . MoI 2 was shown to have the same cluster structure as MoCl 2 , which can be rendered as [(Mo 6 I 8 )I a 2 I a–a 4/2 ] two‐dimensional cluster coordination polymer (Figure ) .…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…It has been claimed since a long time that MoI 3 is isostructural with MoBr 3 , and thus possesses polymeric chains built of MoI 6 octahedra with shared opposite faces: 1 [MoI 6/2 ]∞ with short Mo–Mo bonds along the chain , . This was recently confirmed by careful refinement of the powder diffraction pattern from a sample of MoI 3 obtained by reductive iodination of MoCl 5 with SiI 4 at 150 °C . MoI 2 was shown to have the same cluster structure as MoCl 2 , which can be rendered as [(Mo 6 I 8 )I a 2 I a–a 4/2 ] two‐dimensional cluster coordination polymer (Figure ) .…”
Section: Introductionmentioning
confidence: 72%
“…Even MoI 5 was claimed as a black powder resulting from reaction of MoCl 5 with CH 3 I, C 2 H 5 I or CH 2 I 2 after 15 h heating; the product was characterized by elemental analysis and was found to be ESR‐silent . It has been claimed since a long time that MoI 3 is isostructural with MoBr 3 , and thus possesses polymeric chains built of MoI 6 octahedra with shared opposite faces: 1 [MoI 6/2 ]∞ with short Mo–Mo bonds along the chain , . This was recently confirmed by careful refinement of the powder diffraction pattern from a sample of MoI 3 obtained by reductive iodination of MoCl 5 with SiI 4 at 150 °C .…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Practical experience has shown that the straightforward solid‐state reaction of the elements in fused silica does not proceed in an easy way and requires careful handling, and the corresponding reaction for tungsten is ineffective. [18b] This prompted us to develop new methods for the preparation of W 6 I 12 and Mo 6 I 12 for subsequent ligand‐substitution reactions. At this point, we designed new compounds containing [M 6 I 8 L 6 ] 2– clusters (M = W, Mo) with various ligands (L).…”
Section: Introductionmentioning
confidence: 99%